FLIP-FLOP VERSUS HIGH HEEL ON POSTURE AMONG COLLEGE GOING GIRLS - .V, VELKUMAR; SALAUDEEN, MOHAMED; .S, SENTHIL (International Journal of Psychosocial Rehabilitation, 2021)
The background and purpose of the study are that footwear plays a vital role in posture. Nowadays, students, especially college-going girls, often wear various types of footwear, such as high heels and flip-flops, without being aware of the impact on their posture. Therefore, this study aims to determine the posture variations between wearing high heels and flip-flops among college-going girls. The methodology states that this is an observational study. A hundred samples were recruited from Sri Balaji Vidyapeeth University, Pondicherry, and divided into two groups: Group A consisted of those who had been using flip-flops alone for the last six months, and Group B included those who had been using high heels alone for the last six months. The Reedco Posture Assessment Scale (RPS) was used to assess the posture of all participants, and the data was analyzed using an unpaired t-test in SPSS software. The t-value was 8.49841, and the p-value was less than 0.00001, indicating a statistically significant result at p < 0.05. The study concluded that high heels have a greater effect on posture compared to flip-flops.